Aplicando crowdsourcing na sincronização de vídeos gerados por usuários - Costa Segundo, Ricardo Mendes (2017)
Crowdsourcing is a solve-problem strategy based on collecting contributions with partial results from individuals and aggregating them into a major problem solution. Based on this strategy, this thesis shows how the crowd can synchronize a set of videos generated by users, correlated to an event. Each user captures the event with its personal viewpoint and according to its limitations. In this scenario, it is not possible to ensure that all generated contents have homogeneous characteristics (starting time and duration, resolution, quality, etc.), hindering the use of a purely automatic synchronization process. Additionally, user generated videos are distributed available between several independent content servers. The assumption of this thesis is that the ability of human intelligence to adapt can be used to render a group of videos produced in an uncoordinated and distributed manner generating its synchronization. To prove this hypothesis, the following steps were executed: (i) the development of a synchronization method for multiple videos from independent sources; (ii) The execution of a systematic mapping about the use of crowdsourcing for processing videos; (iii) The development of techniques for the use of the crowd in synchronizing videos; (iv) The development of a functional model for developing synchronization applications using crowdsourcing, which can be extended for general video applications; and (v) The execution of experiments to show the ability of the crowd to perform the synchronization. The results found show that the crowd can participate in the synchronization process and that several factors can influence the accuracy of the results obtained.